Open treatment of condylar fractures via extraoral approaches: A review of complications. Issue 8 (August 2018) - Rozeboom, A.V.J.; Dubois, L.; Bos, R.R.M.; Spijker, R.; de Lange, J.
Abstract: Background: There is considerable controversy about whether condylar fractures should be treated open or closed. Even when there is a clear indication for open treatment, the appropriate approach opens another debate. Purpose: To provide a clear overview on the complications of extraoral approaches to condylar fractures. Methods: Systematic literature search of all indexed years on PubMed, Medline, and Embase. For detailed analysis, we selected 70 studies. Results: Of the 2783 patients who were studied with respect to facial nerve function, 338 (12%) experienced some form of weakness. Most (95%) achieved full recovery. In 17 of the 338 patients (5%), these paralyses were permanent. A hematoma occurred in 1.7%, an infection of the wound in ≥2.9%, Frey syndrome in 1.1%, a sialocele in 2.6%, a salivary fistula in ≥4.8%, sensory disturbance of the great auricular nerve in 7.9%, and an unsatisfactory scar in ≥1.6% of the patients. Conclusion: Due to the great diversity in fractures, approaches, and surgical techniques, it is difficult to objectively compare surgical techniques for condylar fractures and their complications. Based on the literature studied in this review, we propose a treatment protocol with respect to open treatment approaches.